Urban thermal stress climatic mapping: Combination of long-term climate data and thermal stress risk evaluation. (October 2017) - Lin, Tzu-Ping; Chen, Yu-Cheng; Matzarakis, Andreas
Highlights: Thermal conditions in each urban grid are quantified by the measurement and land use. Thermal stress is presented based on occurrence frequency for long-term climate. Regions with dense population and high building density have higher thermal risk. The thermal risk is lower in areas with higher green coverage and lower population. Abstract: Urban thermal stress climatic maps present the features of urban thermal conditions relevant for planning by integrating climate parameters and urban development information. Planners can easily identify thermal environment characteristics and detect existing problems in urban climatic information to make appropriate decisions regarding urban planning processes. In this study, the metropolitan area of Taichung City was chosen as a study area to analyze urban development factors. First, the gridding approach was used to generate a standardized process for constructing a thermal stress map of the study area. Second, basic layers, including population density, land-use zoning, building total floor area, and land cover type, were collected. Third, development layers, including the sky view factor and impervious surface ratio, were established. Fourth, mobile and fixed-point meteorological measurements were obtained twice a month in 2013–2014. The measurement results and layer information were integrated to establish the thermal stress estimation equation through multiple regression analysis. Finally, the long-term climate data of Taichung City were imported into the estimation equation to determine the thermal stress risk and thermal stress potential through the application of a physiologically equivalent temperature. The thermal stress map can demonstrate the link between urban development and human thermal perception, thereby enhancing climate adjustment for urban areas.